Manajemen risiko dalam keamanan informasi dan perlindungan data - Damya, Valentyno (Maliki Interdisciplinary Journal, 2024)
In the rapidly evolving digital era, information security and data protection are crucial for companies worldwide. This article discusses the importance of cybersecurity awareness in the context of corporate risk management, highlighting various types of threats and challenges faced in managing information security risks.Through literature review, this research finds that companies in Indonesia and abroad exhibit varying levels of awareness regarding cybersecurity threats. Stringent regulations, investments in security technologies, and organizational cultures emphasizing privacy and data security are key factors in enhancing this awareness. However, challenges persist, particularly in addressing increasingly sophisticated and complex threats.Collaborative efforts between governments, industries, and relevant institutions are necessary to enhance cybersecurity awareness through education, training, and adoption of best practices in cybersecurity risk management. Only with the right preventive measures and a proactive approach can companies be better prepared to face cyber threats and effectively safeguard their information security.